The children's garden : loads of things to make & grow - Appleby, Matthew (Garden journalist) (Frances Lincoln, 2016)
A garden can be a place for discovery, creativity and fun, and a space that encourages children to enjoy and engage with the natural world. Through 52 exciting family projects, this book inspires parents and their children to play and learn in the garden, with activities including nature trails, cooking, crafting and growing plants and vegetables. Ex-primary teacher Matthew Appleby (author of The Allotment Planner, 2013) is the expert voice behind the book. Appleby has two sons and has tapped into his first-hand experience of parenting and teaching to devise these seasonal projects for every week of the year. The Children's Garden is the perfect companion for families looking to discover the magic and adventure their gardens have to offer.